Ru(iii) complexes with pyrazolopyrimidines as anticancer agents: bioactivities and the underlying mechanisms. Issue 4 (6th January 2022) - Gu, Yun-Qiong; Shen, Wen-Ying; Yang, Qi-Yuan; Chen, Zhen-Feng; Liang, Hong
Abstract : Ruthenium(III) complex with pyrazolopyrimidine inhibited tumor cells proliferation, caused DNA damage by interacting with DNA and inhibition of the Topo I enzyme, induced cell cycle arrest in S phase and apoptosis via mitochondrial dysfunction. Abstract : Three ruthenium(iii ) complexes with pyrazolopyrimidine [Ru(L n )(H2 O)Cl3 ] (1–3, n = 1–3 ) were prepared and characterized. These Ru(iii ) compounds show strong cytotoxicity against six cancer cell lines and low toxicity to normal human liver cells. Particularly, they exhibited stronger cytotoxicity to SK-OV-3 cells than cisplatin. Mechanism studies revealed that complex 1 inhibited tumor cell invasion and suppressed cell proliferation, induced apoptosis by elevating the levels of intracellular ROS (reactive oxygen species) and free calcium (Ca 2+ ), and reduced mitochondrial membrane potential (Δ Ψ ). It also activated the caspase cascade, accompanied with upregulation of cytochrome c, Bax, p53, Apaf-1 and downregulation of Bcl-2. Moreover, complex 1 caused cell cycle arrest at S phase by inhibiting the expression of CDC 25, cyclin A2 and CDK 2 proteins, and induced DNA damage by interacting with DNA and inhibiting the topoisomerase I enzyme. Complex 1 exhibited efficient in vivo anticancer activity in a model of SK-OV-3 tumor xenograft.